2010
DOI: 10.1007/s00586-010-1449-z
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of the fracture level in short segment fixation of thoracolumbar fractures

Abstract: Short segment posterior fixation is the preferred method for stabilizing thoracolumbar fractures. In case of significant disruption of the anterior column, the simple short segment construct does not ensure adequate stability. In this study, we tried to evaluate the effect of inclusion of the fractured vertebra in short segment fixation of thoracolumbar fractures. In a prospective randomized study, eighty patients with thoracolumbar fractures treated just with posterior pedicular fixation were randomized into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
4
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(97 citation statements)
references
References 14 publications
4
87
4
2
Order By: Relevance
“…Later, there were some in vitro biomechanical studies on the pedicle screw at the fracture level, [8,9,24] whose results showed that it could clearly improve the stability of pedicle screw fixation system and decrease the stress distribution on each pedicle screw. Some authors [17,25,26] also suggested that pedicle screw fixation combined with intermediate screw at the fractured vertebrae improved biomechanical stability and achieved better reduction, less correction loss, fewer instrument failures, and comparable or better clinical outcomes. Conversely, Hakalo and Wronski [27] considered that pedicle screw insertion into the fractured vertebra did not effectively increase the spinal axial bearing capacity and initial stability, thus it could not reduce the postoperative correction loss and failure rate of internal fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Later, there were some in vitro biomechanical studies on the pedicle screw at the fracture level, [8,9,24] whose results showed that it could clearly improve the stability of pedicle screw fixation system and decrease the stress distribution on each pedicle screw. Some authors [17,25,26] also suggested that pedicle screw fixation combined with intermediate screw at the fractured vertebrae improved biomechanical stability and achieved better reduction, less correction loss, fewer instrument failures, and comparable or better clinical outcomes. Conversely, Hakalo and Wronski [27] considered that pedicle screw insertion into the fractured vertebra did not effectively increase the spinal axial bearing capacity and initial stability, thus it could not reduce the postoperative correction loss and failure rate of internal fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Farrokhi et al 53 showed similar clinical outcome in their study one level above and one level below excluding the fracture level (bridging group), or including the fracture level (including group) but high rate of instrumentation failure in the ''bridging'' group. The ''bridging'' group showed a mean worsening (29%) in kyphosis, whereas the ''including'' group improved significantly by a mean of 6%.…”
Section: Discussionmentioning
confidence: 73%
“…The loss of correction-which occurred in the first 5 months-was only 2°, less than that reported by Palmisani [33] who reported minimal percutaneous fixation of these fractures without cement. It is of interest to compare this paper with that of Farrokhi et al [14] referred to below. The paper by Pneumaticos et al [36] asks the question as to whether when we do a vertebroplasty should we routinely do a needle biopsy to establish a tissue diagnosis.…”
Section: Vertebroplastymentioning
confidence: 93%
“…The paper by Farrokhi et al [14] deals with the concept that one should include the fracture level with pedicle screws in doing a short segment fixation of a thoracolumbar fracture. Although frequently done by surgeons on the Continent, in the United Kingdom, there is a prejudice against this, and I hope this paper will have a significant clinical impact.…”
Section: Spinal Traumamentioning
confidence: 99%